2022
DOI: 10.1155/2022/2017975
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Serious Games in Attention Rehabilitation and Their Effects

Abstract: Attention is a basic and main mental task and can play an important role in the functioning of other brain abilities such as intelligence, memory, learning, and perception, and its deficit occurs in 80% of patients with traumatic brain injury. The use of game-based tools for rehabilitation is rapidly expanding. Cognitive rehabilitation via video games is an emerging hot topic in cognitive science. Serious games serve a specific purpose in addition to entertainment. They can be more engaging than exercises sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 77 publications
(148 reference statements)
0
20
0
3
Order By: Relevance
“…Games for which entertainment is not the primary goal (e.g., serious game, game-based learning, rehabilitation game, physical training exergame) are designed to help the user achieve a primary goal (e.g., academic learning, training, cognitive rehabilitation, skill enhancement, behavioral change, etc.) that is not inherently related to the player-video game interaction (e.g., Krath et al, 2021;Shahmoradi et al, 2022). The present review aimed to focus on player experience data (including presence) collected in situations uniquely designed to achieve optimal player experience.…”
Section: Literature Searchmentioning
confidence: 99%
“…Games for which entertainment is not the primary goal (e.g., serious game, game-based learning, rehabilitation game, physical training exergame) are designed to help the user achieve a primary goal (e.g., academic learning, training, cognitive rehabilitation, skill enhancement, behavioral change, etc.) that is not inherently related to the player-video game interaction (e.g., Krath et al, 2021;Shahmoradi et al, 2022). The present review aimed to focus on player experience data (including presence) collected in situations uniquely designed to achieve optimal player experience.…”
Section: Literature Searchmentioning
confidence: 99%
“…Computerized games can be more engaging than routine exercises, because they replace reward and motivation systems with real-world motivations as a complement to rehabilitation activities. People can be immersed in the game world, and their ability and knowledge can be improved without any danger [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…et al In this contribution, the authors provide an overview of applying serious games in attention rehabilitation in patients with traumatic brain injury. This review, however, focused specially on other disorders, not ASD [ 31 ]. Patricia Mesa-Gresa et al published a systematic review that focused mainly on the effectiveness of virtual reality for children and adolescents with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Schöbel et al (15) presented a bibliometric analysis of existing literature on game concepts in digital learning and Hallinger et al (16) conducted a bibliometric analysis on simulations and SGs in educating for sustainability, that both studies focused on the application of SGs in education. Also, some recent systematic reviews have reported the effectiveness of SGs in the fields of rehabilitation (17), psychotherapy (18), and education (19). There were several scoping review exploring SGs for rehabilitation in terms of stroke rehabilitation (20), upper extremity rehabilitation (21), musculoskeletal diseases rehabilitation (22), and so on.…”
Section: Introductionmentioning
confidence: 99%